Intelligent Planning Framework for Star-Walk Mission Based on Multimodal Observation Requirements Information - Guangxi ZHU; Gang WANG; Chao ZHANG; Yingte CHAI; Wei FU; Zhengqiang GUO (天地一体化信息网络)
Combined with the current requirement and research for rapid intelligent planning of star-walk observation mission, and a framework based on multimodal observation requirements such as voice and text was designed.The framework aimed to satisfied the requirements and focued on breaking through three key issues for future emergency rescue applications: multimodal requirement interpretation, full-elements resource coordination and complex emergency missions planning, and to open the automatic link between observation requirement, resource planning and mission planning by making full use of deep learning methods.On these bases, the framework had the ability to provided rapid remote sensing observation information with a specified time and made full play to the comprehensive eff ectiveness of remote sensing information resources.